Association of household child care practices and stunting of set 1 children beneficiaries of the Pantawid Pamilyang Pilipino Program in Pasay City a nested case control study - Develos, Maribel M.
Background: The quality of childcare is one of the underlying determinants of stunting in children. It is a challenging task particularly for caregivers in poor resource settings. The Pantawid Pamilyang Pilipino Program (4Ps) is a social protection program that aims to improve the beneficiaries' caregiving practices which could compensate for the negative effects of poverty on children's nutritional status. Objective: This study was conducted to determine the childcare practices (CCP) of the 4Ps beneficiaries in an urban setting, and to explore the association of good CCP with stunting. Design: A nested case control study was conducted to achieve the study's objectives. The cohorts were the children enrolled in the program when they were 0 to 24 months old at the start of program implementation in 2008. The cases were the stunted children while the controls were children with normal anthropometric measurements. Exposure variable was the household CCP (HH CCP). Exposed children were those whose families have desirable overall CCP; unexposed children were those whose families have undesirable CCP. Setting: Tha sampling population consisted of Set 1 households of Pasay City with eligible children beneficiaries. A total of 82 stunted children and 97 normal children were included in the study. Pasay City was chosen because it was one of the first two cities in Metro Manila where the 4Ps was first implemented. Measurements: The dependent variable was the child's height-for-age z score (HAZ). The main exposure variable was household CCP, which is an index derived from 17 component variables based on the WHO essential nutrition actions. Child, primary caregiver, and household characteristics, including the caregiver and household well-being status, were collected and included in the analysis. Multiple logistic regression was performed to determine the association between overall desirability of HH CCP and stunting. Multiple linear regression analysis was done to explore the relationship between HH CCP score and HAZ. Results: Stunted children significantly had lower mean birth weight than normal children. Mothers of stunted children were shorter than mothers of nirmal children, and there were more caregivers of stunted children who perceived themselves aspoor compared with controls. Mean monthly income was also smaller among HH with stunted children. Six out of 10 beneficiaries were found to have ?desirable? CCP. Desirable CCP is significantly associated with stunting (OR 0.30; 95% CI 0.13; 0.70; p value = 0.005). Multiple regression analysis showed that HH CCP has a significant positive relationship with HAZ score among children beneficiaries. Conclusion: Desirable CCP among 4Ps household beneficiaries decrease the likelihood of stunting among children. Implementers of 4Ps should therefore focus on improving further the childcare practices of beneficiaries in order to decrease the prevalence of stunting among children.